An Empirical Study of MEH in China's Stock Market - Li, Jing (2007)
MEH (Market Efficiency Hypothesis) has been discussed for several decades in world wide with has proposed by Fama in his PHD dissertation in 1965. This paper examines whether the market is efficient and to what extent the market is efficient in China's Stock Market. For statistic tests are applied involving unit root test, run test, serial correlation test and gradual efficiency test. According to the results of the tests on daily close price of eight indices in Shanghai stock exchange for five years, China's Stock market can be concluded to be weak form efficient and the efficiency is enhanced with the time.